Oedipus : or, the legend of a conqueror - Delcourt, Marie (Studies in Violence, Mimesis and Culture Ser, 2020)
Intro -- Contents -- Foreword-Vinciane Pirenne-Delforge -- Translator's Note -- Introduction -- Chapter 1. Exposure of the Infant -- Chapter 2. Murder of the Father -- Chapter 3. Victory over the Sphinx -- Chapter 4. The Riddle -- Chapter 5. Marriage to a Princess -- Chapter 6. Incest with the Mother -- Endings -- Myths and Memory -- Appendix 1. The Pisander Scholion and Related Summaries -- Appendix 2. Legends and Cults of Twin Children -- Appendix 3. Animal Tales in Greece -- Appendix 4. The Religious Significance of Spoils in the Homeric Poems -- Notes -- Addenda -- Index of Passages Cited -- Index.